Revisiting the Curse: Resource Rent and Economic Growth of Sub-Sahara African Countries - Yang, Shu; Abdulahi, Elyas; Haider, Muhammad Afaq; Khan, Muhammed Asif (International Journal of Economics and Financial Issues, 2019)
This paper empirically verifies the drivers of economic growth of resource abundant Sub Sahara African countries (SSA) and examines the extent to which they are typical or unique to the resource curse hypothesis. To this end, using an econometric model of Driscoll-Kraay an assessment is made on a sample of 22 resource-rich Sub-Saharan African countries over the period 1998–2016. The result contradicts the argument of the resource curse due to a positive and significant relationship between resource rent, institutional quality, and economic growth. Nevertheless, the study provides evidence of the curse through the exchange rate, foreign debt, and education. The results are also robust under alternative econometrics estimation model of IV-2SLS and GMM-System. Keywords; resource curse, resource rent, sluggish economic growth JEL Classification: Q DOI: https://doi.org/10.32479/ijefi.7177